Refinement of Taxpayer Legal Subject provisions in the New Criminal Code against the Offence of Corporate Tax Avoidance in Indonesia - Kusworo, Daffa Ladro (Faculty of Law, Universitas Lampung, 2023)
Law No. 16 of 2009 concerning General Provisions and Tax Procedures (UU KUP) focuses on corporate criminal liability and criminal sanctions related to criminal offenses in the field of taxation. This stems from criminal responsibility to corporations as a prerequisite for corporate punishment. Criminal acts in the field of taxation are regulated in the KUP Law in terms of legal subjects covered by the KUP Law and criminal sanctions in the event of a violation of the criminal act, but there are inconsistencies in criminal liability for corporations and criminal sanctions regulated in Articles 38, 39, and 39A UU KUP, thus creating uncertainty in law enforcement. In addition, corporate law enforcement has no basis for calculating the conversion of substitute imprisonment if the defendant is unable to fulfill the fine as stipulated in the decision. The research method used is normative juridical which refers to laws and regulations regarding taxation accompanied by literature studies in the form of books, journals, and others. Data analysis was carried out through a qualitative descriptive approach to describe legal phenomena that occur in order to find solutions to problems through a specific conclusion. The results of the study show that the formulation of offenses in the KUP Law is actually inconsistent with the theories of criminal responsibility in the context of criminal law, even though Articles 38, 39, 39A and 43 are intended to regulate criminal provisions in the field of taxation. The problems of the judge's decision above can be resolved when in the future the New Criminal Code is implemented, which substantially explains in detail legal subjects in classification by using cumulative punishment. seen from the articles that have corporate elements in Articles 45-50 Criminal code.